2021
DOI: 10.1186/s12905-021-01339-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and determinants of vitamin D deficiency among premenopausal and postmenopausal women in Karachi Pakistan

Abstract: Background Vitamin D deficiency is becoming a serious public health problem, even in sun-drenched cities like Karachi, Pakistan. We investigated the prevalence of vitamin D deficiency and its association with sociodemographic characteristics, anthropometric measures, and lifestyle factors among premenopausal and postmenopausal women (n = 784). Methods Face-to-face interviews were conducted to collect information and serum concentrations of 25-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Our results illustrate that the majority of the study participants were in the deficiency zone (68.4%). This, in accordance with published literature, demonstrates the high frequency of VDD in Pakistani women in the reproductive age group [15]. A study from Pakistan demonstrated that despite being a year-round sunny environment, VDD has been reported to be alarmingly high among women.…”
Section: Discussionsupporting
confidence: 89%
“…Our results illustrate that the majority of the study participants were in the deficiency zone (68.4%). This, in accordance with published literature, demonstrates the high frequency of VDD in Pakistani women in the reproductive age group [15]. A study from Pakistan demonstrated that despite being a year-round sunny environment, VDD has been reported to be alarmingly high among women.…”
Section: Discussionsupporting
confidence: 89%
“…Pakistan is having the highest prevalence rate of 15 vitamin-D deficiency in South East Asia. In the general population, 57-58% of women reported having vitamin-D 16,17 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, we found that females aged 18-30 and no milk use were independent predictors of VDD. Previously, a number of studies have reported an association between age and VDD [38][39][40][41][42]. A study in children and adults from Saudi Arabia found a modest but positive correlation between Vit-D level and dairy product consumptions [43].…”
Section: Discussionmentioning
confidence: 99%